The maid behind "The Handmaid’s Tale": A tainted view of Half-hanged Mary - Chatterjee, Anirban (Research and Humanities in Medical Education, 2015)
Although much has been debated about the role of syphilis in the witch hunting craze that swept across Europe in the 16th and 17th Century, the equally horrifying Witch Trials in the United States of America were all bracketed under the common heading of ergotism. Here, I focus on one specific case in particular, which is peculiar owing to many factors, not the least being the fact that the woman who was hanged after being accused of witchcraft, eventually lived!